2016
DOI: 10.1016/j.celrep.2016.06.103
|View full text |Cite
|
Sign up to set email alerts
|

MLKL and FADD Are Critical for Suppressing Progressive Lymphoproliferative Disease and Activating the NLRP3 Inflammasome

Abstract: MLKL, a key component downstream of RIPK3, is suggested to be a terminal executor of necroptosis. Genetic studies have revealed that Ripk3 ablation rescues embryonic lethality in Fadd- or Caspase-8-deficient mice. Given that RIPK3 has also been implicated in non-necroptotic pathways including apoptosis and inflammatory signaling, it remains unclear whether the lethality in Fadd(-/-) mice is indeed caused by necropotosis. Here, we show that genetic deletion of Mlkl rescues the developmental defect in Fadd-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 52 publications
(83 reference statements)
5
71
1
Order By: Relevance
“…Our findings do not challenge the existence of these pathways; rather, they indicate that, irrespective of upstream signaling events, activation of MLKL leads to processing and activation of IL-1β. These findings may explain the recently-reported defects in NLRP3 inflammasome activation in macrophages lacking MLKL(26). Our findings indicate an inextricable link between the execution of necroptosis and the release of IL-1β, and implicate bioactive IL-1β and IL-18 as likely effectors of inflammatory responses to the necroptotic death of myeloid cells.…”
Section: Discussionsupporting
confidence: 56%
“…Our findings do not challenge the existence of these pathways; rather, they indicate that, irrespective of upstream signaling events, activation of MLKL leads to processing and activation of IL-1β. These findings may explain the recently-reported defects in NLRP3 inflammasome activation in macrophages lacking MLKL(26). Our findings indicate an inextricable link between the execution of necroptosis and the release of IL-1β, and implicate bioactive IL-1β and IL-18 as likely effectors of inflammatory responses to the necroptotic death of myeloid cells.…”
Section: Discussionsupporting
confidence: 56%
“…Along these lines, even though the loss of both RIPK3 and caspase-8 alleviates many acute injuries, it leads to autoimmune disease, which is further exacerbated in Mlkl -/- ; caspase-8 -/- animals [112, 113]. Overall, we interpret these and other published data to indicate that effector mechanisms activated by RIPK1 kinase are carefully balanced and their modulation should be considered with caution as it may fundamentally change the wiring of the regulation, leading to unexpected detrimental responses.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups observed that while Mlkl -/- rescued embryonic lethality due to activation of necroptosis in Caspase-8 -/- and Fadd -/- mice, these mice rapidly succumbed to extremely severe systemic autoimmune disease, lymphadenopathy, and thrombocytopenia [112, 113]. Interestingly, while the development of autoimmunity may be hypothesized to result from a deficiency of both apoptosis and necroptosis in these mice; however, cell death-deficient Ripk3 -/- ;Caspase-8 -/- and Ripk3 -/- ; Fadd -/- mice developed much milder autoimmune disease.…”
Section: Disease Pathologymentioning
confidence: 99%
“…This excess cell death that destroys the vasculature of the embryo, leading to developmental arrest around E10.5 (Varfolomeev et al 1998;Yeh et al 1998Yeh et al , 2000, can be fully rescued by codeletion of RIPK3 or MLKL, the key driver and effector of necroptosis, respectively. FADD/MLKL-deficient and Caspase 8/MLKL-deficient mice, which lack literally all DR-mediated apoptosis as well as programmed necroptosis are born at a normal Mendelian frequency and show no developmental abnormalities, as do mice lacking FADD plus RIPK3 or Caspase 8 plus RIPK3 (Kaiser et al 2011;Oberst et al 2011;Alvarez-Diaz et al 2016;Zhang et al 2016). Tissue homeostasis also appears unaffected in these mice, with one notable exception, the hematopoietic compartment, which gradually expands and provokes fatal autoimmunity in aged mice (Alvarez-Diaz et al 2016;Zhang et al 2016).…”
Section: Mitochondrial Apoptosis As a Regulator Of Tissue Homeostasismentioning
confidence: 95%
“…FADD/MLKL-deficient and Caspase 8/MLKL-deficient mice, which lack literally all DR-mediated apoptosis as well as programmed necroptosis are born at a normal Mendelian frequency and show no developmental abnormalities, as do mice lacking FADD plus RIPK3 or Caspase 8 plus RIPK3 (Kaiser et al 2011;Oberst et al 2011;Alvarez-Diaz et al 2016;Zhang et al 2016). Tissue homeostasis also appears unaffected in these mice, with one notable exception, the hematopoietic compartment, which gradually expands and provokes fatal autoimmunity in aged mice (Alvarez-Diaz et al 2016;Zhang et al 2016). As such, all of these mutants mimic the pathology noted in lpr mutant mice that lack functional FAS/CD95 but develop normally otherwise (Watanabe-Fukunaga et al 1992).…”
Section: Mitochondrial Apoptosis As a Regulator Of Tissue Homeostasismentioning
confidence: 99%